A review of how leadership justice, and job satisfaction interact to shape counterproductive work behavior - Pradikto, Arhamedho Akbar Panotonagoro R.; Prasetya, Arik; Hutahayan, Benny (Annals of Human Resource Management Research, 2025)
Purpose: This review explores the interplay between leadership, job satisfaction, organizational justice, and counterproductive work behavior (CWB) in organizational settings. Research Methodology: The analysis synthesizes findings from various studies, focusing on the Leader-Member Exchange (LMX) theory and its implications for job satisfaction and CWB. A total of 14 articles were reviewed: four focused on LMX's impact on job satisfaction and CWB, five examined the role of organizational justice in shaping these variables, and five investigated the mediating role of job satisfaction in the LMX-CWB relationship. Results: The review highlights that positive LMX relationships, characterized by trust, respect, and mutual commitment, significantly enhance job satisfaction and reduce CWB. The findings underscore the importance of fostering positive LMX interactions and ensuring fairness in organizational processes to mitigate CWB. Conclusions: The study concludes that Effective leadership and organizational justice are vital for promoting job satisfaction and minimizing counterproductive behaviors in the workplace. Understanding these dynamics is essential for creating healthier and more productive work environments. Limitations: One limitation of this review is that it primarily focuses on existing literature, which may not encompass all relevant studies or perspectives on the topic. Contribution: This review contributes to the field of organizational behavior and management by providing a comprehensive understanding of how leadership and organizational justice influence employee attitudes and behaviors. This finding offers valuable insights for academics and practitioners aiming to address CWB and enhance workplace dynamics.